American genesis: the antievolution controversies from Scopes to creation science - Moran, Jeffrey P. (Oxford University Press, 2012)
"In American Genesis, Jeffrey P. Moran explores the ways in which the evolution debate has reverberated beyond the confines of state legislatures and courthouses. Using extensive research in newspapers, periodicals, and archives, Moran shows that social forces such as gender, regionalism, and race have intersected with the debate over evolution in ways that shed light on modern American culture."--Jacket